El descubrimiento del Nuevo Mundo en dos obras rabínicas sefardíes de Salónica (siglo XIX) - Šmid, Katja (Ars et humanitas, 2017)
The aim of this article is to deal with the issue of the discovery of the New World in two Judeo-Spanish works, published in Hebrew Rashi script in Salonika in the midnineteenth century. On the one hand, we examine Sefer Darkhe ha-adam (Salonika, 1843), a moralistic Sephardi work, written by Yishac Bekhor Amarachi and Yosef ben Meir Sasson, and, on the other hand, Sefer ha-erit (Salonika, 1847), a fascinating Judeo-Spanish work on science, mysticism and morality. By examining selected excerpts of these works, we try to analyse several episodes in the discovery of America, such as, for example, scientific advances in navigation, especially those related to the invention of the compass, the discovery of the New World, the encounter between Spaniards and the native population, and the exploration of life on the new continent.
Keywords: Darhe haabam; odkritje Amerike; plovstvo; sefardska književnost; Sefer haberit